Systematic Changes in China - Zha, Qiang; Wang, Chuanyi (International Higher Education, 2014)
Two parallel and discrete sectors seem to be emerging in Chinese higher education, both extending to university level. One is academic and “cosmopolitan” in outlook, and supports intensive research. The other is local, and teaching and service oriented. While such a binary approach helps diversify the interpretation of higher education quality and contributes to its relevance, it remains to be tested if China’s tradition of meritocracy and elitism could ultimately drive changes back in the academic direction.